MHD flow of walters` liquid b over a nonlinearly stretching sheet - Siddheshwar, Pradeep G.; Mahabaleshwar, U.S.; Chan, Andy (Zielona Góra: Uniwersytet Zielonogórski)
The paper discusses the boundary layer flow of a weak electrically conducting viscoelastic Walters` liquid B over a nonlinearly stretching sheet subjected to an applied transverse magnetic field, when the liquid far away from the surface is at rest. The stretching is assumed to be a quadratic function of the coordinate along the direction of stretching. An analytical expression is obtained for the stream function and velocity components as a function of the viscoelastic parameter, the Chandrasekhar number and stretching related parameters. The results have possible technological applications in liquid based systems involving stretchable materials.
Keywords: analytical solution; magnetic field; nonlinear stretching sheet; Walters` liquid B